Can Encroachment Benefit Hotel Franchisees? - Kim, TI Tongil; Jap, Sandy D. (Journal of Marketing, 2022)
Franchise encroachment, or the addition of an outlet in the vicinity of existing franchisees, is largely viewed as resulting in revenue cannibalization of incumbent locations. Against this backdrop, the authors consider the possibility that the addition of same brand outlets can, in fact, also create positive effects via customer utility and ultimately benefit franchisees, due to a range of mechanisms such as quality signaling, learning, or brand awareness, resulting in a positive pathway on franchisee performance. The authors unpack this possibility using an experiment and detailed proprietary and publicly available data sets from the hotel industry over a five-year period. Their results show evidence of positive effects on customer utility for same-brand outlets and stronger effects for newer brands, cross brands, and online travel agency channel bookings. Counterfactual simulations indicate that although encroachment hurts franchisees on average, it can modestly benefit same-brand franchisees in low-brand-density markets. Together, the findings illustrate the potential “sunny side” of encroachment, underscoring the need to update our view of encroachment as context-dependent. The novel emphasis on customers versus the dominant firm view suggests customer and incumbent responses to encroachment should be accounted for in the development of franchise strategy and public policy decisions.